EMBR-02. RECURRENT HOMOZYGOUS DELETION OF DROSHA AND MICRODUPLICATION OF PDE4DIP CONTAINING THE ANCESTRAL DUF1220 DOMAIN IN PINEOBLASTOMA. Issue 2 (22nd June 2018) - Snuderl, Matija; Kannan, Kasthuri; Pfaff, Elke; Wang, Shiyang; Stafford, James; Serrano, Jonathan; Heguy, Adriana; Ray, Karina; Faustin, Arline; Aminova, Olga; Dolgalev, Igor; Stapleton, Stacie; et al.
Abstract: BACKGROUND: Pineoblastoma is a rare and highly aggressive brain cancer of childhood, histologically belonging to the spectrum of primitive neuroectodermal tumors. Patients with germline mutations in DICER1, a ribonuclease involved in microRNA processing, have increased risk of pineoblastoma, but genetic drivers of sporadic pineoblastoma remain unknown. METHODS: We analyzed pediatric and adult pineoblastoma samples (n=23) using integrated genomic studies, including genome-wide DNA methylation profiling, whole-exome or whole-genome sequencing, and whole-transcriptome analysis. RESULTS: Pediatric and adult pineoblastomas showed distinct methylation profiles, the latter clustering with lower grade pineal tumors and normal pineal gland. Recurrent somatic mutations were found in genes involved in PKA- and NF-κB signaling, as well as in chromatin remodeling genes. We identified recurrent homozygous deletions of DROSHA, acting upstream of DICER1 in microRNA processing, and a novel microduplication involving chromosomal region 1q21 containing PDE4DIP (myomegalin), comprising the ancient DUF1220 protein domain. Expression of PDE4DIP and DUF1220 proteins was present exclusively in pineoblastoma with PDE4DIP gain. Whole-transcriptome analysis showed that homozygous loss of DROSHA led to distinct changes in RNA expression profile. Disruption of the DROSHA locus in human neural stem cells using the CRISPR/Cas9 system, led to decrease of the DROSHA protein, and massive loss of miRNAs. CONCLUSION: We identified recurrent homozygous deletions of DROSHA in pineoblastoma, suggesting that different mechanisms disrupting miRNA processing are involved in the pathogenesis of familial versus sporadic pineoblastoma. Furthermore, a novel microduplication of PDE4DIP leading to upregulation of DUF1220 protein suggests DUF1220 as a novel oncogenic driver in pineoblastoma.